80 TAHUN NEGARA HUKUM: REFLEKSI ATAS UPAYA PENEGAKAN HUKUM BERKEADILAN DAN BERLANDASKAN PANCASILA MENUJU INDONESIA EMAS 2045 - Udiyo Basuki (Kajian Hukum, 2025)
The day after Indonesia proclaimed its independence on August 17, 1945, the Indonesian constitution, the 1945 Constitution, officially came into effect on August 18, 1945. Several of its provisions affirmed Indonesia's status as a state based on law. The proclamation itself, meaning "the source of all things," served as the source of the new legal order. Thus, both strengthened Indonesia's position as a state based on law, with a new legal order and a unique concept of the rule of law: the Pancasila rule of law, a state whose spirit of law enforcement is grounded in the values of Pancasila. Such law enforcement is crucial given that the Pancasila state foundation, as formulated in the Preamble to the 1945 Constitution, serves as a guideline for achieving the nation's goals. Achieving these goals becomes particularly urgent when aligned with the spirit of welcoming Indonesia Emas 2045, which serves as a program and vision for society, nation, and state.